Privatization and Entrepreneurship : The Managerial Challenge in Central and Eastern Europe /: The Managerial Challenge in Central and Eastern Europe. (2020) - Kaynak, Erdener; Lewis, Alfred; Ullmann, Arieh A
No abstract available